Nutritional and Phytochemical Study of Ilex paraguariensis Fruits - Laura Cogoi; M. Silvia Giacomino; Nestor Pellegrino; Claudia Anesini; Rosana Filip (Journal of Chemistry)
Yerba mate is defined as the product constituted by the dried, slightly roasted, and milled leaves of Ilex paraguariensis. However, the fruits of this species are often found in the commercial product. Nowadays the fruits are considered a byproduct. The objective of this work was to obtain the preliminary data of minerals, lipids, methylxanthines and polyphenols in the ripe fruits of I. paraguariensis. The results showed a considerable amount of total dietary fiber (42.0 ± 1.6 g/100 g) and nutritionally valuable minerals: potassium (1324 ± 15 mg/100 g), iron (6.4 ± 0.5 mg/100 g), magnesium (168 ± 15 mg/100 g), calcium (150 ± 12 mg/100 g), copper (1.1 ± 0.1 mg/100 g), zinc (2.3 ± 0.3 mg/100 g), and sodium (1.3 ± 0.1 mg/100 g). The lipid content was 4.5 g/100 g. Oleic acid was the predominant unsaturated fatty acid (38.74 ± 0.75 g/100 g). Linoleic acid (1.83 ± 0,01 g/100 g) was also present. Methylxanthines were quantified: caffeine (0.118 ± 0.001) and theobromine (0.0125 ± 0.0002) g/100 g. The total polyphenol content was 0.717 ± 0.001 g/100 g. The results obtained in this work suggest the potential value of the fruits of I. paraguariensis for the development of novel products in the food and pharmaceutical industries. This paper aims to contribute to the scientific knowledge of a natural by-product from industry regarding the need of foods and medicines for the new millennium.